Bismuth-mediated arylation - Jurrat, Mark (2019)
Initial efforts were focused on the development of a catalytic protocol for the arylation of hydroxyarenes using Ar3BiX2 reagents. The individual steps oxidation, arylation and transmetallation were investigated separately to be combined in the final step. While the arylation of phenolic substrates results in low overall yields and selectivities, switching to 2- naphthol improved yields drastically, allowing for a mechanistic investigation into the rate and selectivity determining step of the oxidative arylation, the role of electronic properties of substrate and transferred aryl group, as well as the counter ion on the bismuth centre. The diaryl bismuth reaction product was identified and conditions for transmetallation from organoboron reagents to result in a Ar3Bi compound were developed. While oxidation of the Bi(III) reagent could be achieved efficiently with a variety of oxidising agents, a combination of the three steps proved unsuccessful due to the inherent incompatibility of the necessary reagents, precluding development of a catalytic application of bismuth. For a stepwise stoichiometric approach, a variety of bismacylic compounds have been prepared and tested concluding in a thiabismine dioxide core. Different bismacycle (pseudo)- halide salts of the thiabismine dioxide core have been prepared and their capability for transmetallation have been investigated. The reaction proceeds via a μ-oxo intermediate under basic conditions using readily available boronic acids. With a scope involving electron rich to electron poor aryl motifs as well as sterically demanding and even heterocyclic rings, a simple and robust transmetallation protocol has been developed. The subsequent oxidation and arylation was achieved using mCPBA as the oxidant with 2-naphthol as the initial substrate. Notably, no base is required in the arylation process. The scope was extended to numerous naphtholic and phenolic substrates. Mechanistic investigations of all significant processes have been conducted allowing for unprecedented insight into bismuth-mediated arylation, that provide a deeper understanding and provides a priori prediction for untested substrate combinations.